A VIRTUAL STORE FRAMEWORK MODEL: OPTIMISING TRAVEL ROUTE FOR A PASSENGER RAIL OPERATION OF MAINTENANCE COMPONENTS USING GIS - Fourie, Cornelius Jacobus; Chimusoro, Oliver; Asekun, Olabanji Olumuyiwa (The South African Journal of Industrial Engineering, 2018)
Previous studies of supply chain management systems have attempted to focus on transportation, logistics, storage space planning, and time-to-delivery. The biggest challenge for large organisations like the Passenger Rail Agency of South Africa, which has a presence throughout South Africa, is trying to manage all stores efficiently and effectively. This article looks at these challenges, and provides a virtual store framework model to understand the scope and magnitude of an integrated logistics model approach. Geographical information systems were applied to the virtual store to determine an efficient route for transporting components between stores. Furthermore, the authors identified the major aspects and impacts of a virtual store system in a rail passenger transport operation. This was done through on-site studies and a review of the literature on virtual stores. The model was tested on a case study that produced results that include time and cost as the variables for decision-making.